Prototype Design of Micro Hydro Power Plant with Utilization of Irrigation Water in Rice Fields Based on IoT - Wike Handini; Nurdina Widanti; Sri Wiji Lestari; Ahmad Raafi Haqq; Ahmad Hafizh; Bagus Mulyadi (Jurnal Penelitian Pendidikan IPA, 2024)
Irrigation water on the rice field embankments aims to irrigate the rice fields properly, in this study irrigation water is increased not only as a source of water for rice growth but also as an electricity supply around the rice fields. Water will drive a turbine connected to a DC generator to produce a DC electricity source. Then the electricity generated will be monitored using the IoT (Internet of Things) application. The results obtained areof 12 volts, with a water height of 0.98 meters, a water volume of 0.22 m3, and from these results the system can provide electricity supply for smart farming which is applied around the rice fields, from these results it is hoped that rice production can increase and also farmer independence in electricity supply can be created